Formulation of Metarhizium pinghaense and Metarhizium robertsii and the infection potential of the formulations against Pseudococcus viburni (Hemiptera: Pseudococcidae) after storage - Mathulwe, Letodi Luki; Malan, Antoinette Paula; Stokwe, Nomakholwa Faith (African Entomology, 2023)
Formulation of entomopathogens refers to the mixing of various inert ingredients, like clays and mineral oils, with the active ingredients which are the entomopathogens. Successful formulation enhances the survival of the entomopathogen and also eases their transportation, storage, preparation and application. The aim of this study was to develop a formulation to maintain the longevity and pathogenicity of the mass-produced conidia of local Metarhizium pinghaense and M. robertsii, for above-ground future commercial field application against Pseudococcus viburni. The objectives were to develop a cost-effective protocol for formulation of infective propagules and to test their effectiveness under laboratory conditions. The conidia of both isolates were formulated using four different oils (liquid paraffin, coconut, canola and olive oils) as liquid carriers, and diatomaceous earth as a mineral carrier. Conidial viability and pathogenicity were assessed over a period of eight weeks. In the study, it was observed that the conidia formulated in oil carriers maintained a high conidial viability and survival rate of >95 % over a period of eight weeks for both isolates, relative to when formulated in mineral carriers, or when stored as dry conidial powder. The conidia in all the oil formulations were also observed to induce high mortality, ranging between 60 % and 90 % for M. pinghaense, and between 70 % and 90 % for M. robertsii, when used against P. viburni. The ability of conidia of both isolates to maintain viability and pathogenicity, following storage in the oil formulations, increased the likelihood of the local isolates being successfully integrated as biological control agents for management of P. viburni  under field conditions.